2018
DOI: 10.1007/s12603-017-0887-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral health indicators for risk of malnutrition in elders

Abstract: Elders' tooth loss and unmet treatment need for dental caries were associated with compromised quality of life, which indicated increased likelihood for malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
0
37
0
3
Order By: Relevance
“…Ageing is the cause of several health concerns. Older adults face: (1) frailty and mobility difficulties due to arthritis and osteoporosis, (2) a proneness to falls due to sarcopenia, (3) chronic diseases such as obesity, cardiovascular disease, type 2 diabetes, and cancer, (4) decreasing impairments in mental health such as Alzheimer’s disease, depression, and dementia, and (5) poor eyesight and dentition [ 2 ]. In addition, some older adults experience decreased appetite and/or food intake [ 3 , 4 ].…”
Section: Introduction: Ageing and Risks Of Malnutritionmentioning
confidence: 99%
“…Ageing is the cause of several health concerns. Older adults face: (1) frailty and mobility difficulties due to arthritis and osteoporosis, (2) a proneness to falls due to sarcopenia, (3) chronic diseases such as obesity, cardiovascular disease, type 2 diabetes, and cancer, (4) decreasing impairments in mental health such as Alzheimer’s disease, depression, and dementia, and (5) poor eyesight and dentition [ 2 ]. In addition, some older adults experience decreased appetite and/or food intake [ 3 , 4 ].…”
Section: Introduction: Ageing and Risks Of Malnutritionmentioning
confidence: 99%
“…A higher number of MT was associated with a low GOHAI score at the bivariate level. Some previous studies reported that tooth loss was associated with OHRQoL in elderly people [49,50]. Tooth loss lowered diet quality [51] and contributed to the prevalence of dysphagia [52].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss may influence nutritional status . Tooth loss leads to decline in masticatory function, which is the ability to break food boluses down into portions by chewing in order to swallow them .…”
Section: Introductionmentioning
confidence: 98%